A Banff Component Scoring-based Histologic Assessment of Bortezomib-based Antibody-mediated Rejection Therapy. Issue 8 (August 2015) - Sadaka, Basma; Ejaz, Nicole S.; Shields, Adele R.; Cardi, Michael A.; Wadih, George; Witte, David; Abu Jawdeh, Bassam G.; Alloway, Rita R.; Woodle, E. Steve
<x xml:space="preserve">Abstract</x> Background Histology remains a cornerstone for antibody-mediated rejection (AMR) diagnosis. Little data exist supporting histology for assessing therapeutic responses. This study evaluates histologic components in assessing AMR therapeutic responses. Methods Antibody-mediated rejection was diagnosed using Antibody Working Group criteria and Banff component scoring, and C4d staining data were analyzed. Statistics included independent and paired samples t test, χ2, Fisher exact, or the Wilcoxon-signed rank test. Fifty-five AMR patients were analyzed. Early AMR was defined as occurring within 6 months after transplantation and treated with a single rituximab dose and 4 bortezomib doses preceded by plasmapheresis. Allograft biopsies were performed within 48 hours of treatment; repeat biopsy was performed 14 to 21 days later. Results Early AMR demonstrated histologic improvement in mean scores for acute Banff components glomerulitis (g), C4d, g+ peritubular capillaritis (ptc) and acute composite score, but showed deterioration in chronic Banff components tubular atrophy and interstitial fibrosis. Late AMR showed improved mean scores for acute Banff components tubulitis, interstitial inflammation, g, ptc, g + ptc, C4d, and acute composite score, but chronic scores did not change. Significant changes in distribution of Banff scores after treatment were observed for g, C4d, tubular atrophy, and interstitial fibrosis scores in early AMR patients and tubulitis, interstitial inflammation, g, ptc, and C4d in late AMR. Conclusions These results show that: (1) Banff component scoring provides insights into histologic responses to AMR therapy and may provide a potential endpoint for clinical AMR trials. (2) Early and late AMR demonstrate differences in acute and chronic Banff components at the time of the AMR diagnostic biopsy, as well as differential responses to AMR therapy.